Musculoskeletal pain index and quality of life assessment in university students in western Pará (Research, Society and Development, 2022)
Objective: The objective of this study is to evaluate the influence of musculoskeletal pain and sociodemographic factors on the quality of life of college students. Methodology: This is a descriptive, cross-sectional, quantitative research. The research was carried out in a Public University, in the city of Santarém-PA, 30 students participated, belonging to the courses of Physiotherapy and Medicine, which are students of the active methodology and who are definitely enrolled in the courses of Medicine or Physiotherapy and active in the courses. The collection will be carried out using three questionnaires: Modified Sociodemographic, Nordic and WHOQOL-BREF. Results: The health undergraduate students were investigated and this study showed a large percentage of musculoskeletal complaints, where students reported one or more body regions with some pain complaint, and the regions in which there were more pain complaints were head region (2.55), neck-trapezius (2.48) and with emphasis on the lumbar region (2.69). As for the WHOQOL-BREF questionnaire scores, most fit into the regular range with a variable average (3.03 to 3.79), with only the DF score (2.99) needing improvement. Final Considerations: From the research, it is possible to highlight that musculoskeletal pains in the head, neck, trapezius and lumbar regions are the most frequent, and also those with the highest pain intensity. Pain crises predispose to a lower quality of life, thus, the academics of the present HEI may not reach the expected quality of life, while pursuing the dream of a university education.